Eyelid Edema: A Rare Cause of a Common Sign - Andreia Soares; Cristina Almeida; Cristina Freitas; Marco Sales-Sanz; Sara Ribeiro (Case Reports in Ophthalmological Medicine)
We report a 48-year-old female patient who presented to the emergency room with right eyelid edema, with 3 days of evolution. She had suffered minor trauma to this eye one week before. She reported episodes of right eyelid swelling of spontaneous resolution since the occurrence of a traumatic brain injury 5 years ago. Ophthalmological examination showed a soft and painless eyelid edema of the right eye. Brain computed tomography showed an area of bone discontinuity of the orbital roof with brain herniation and a CSF leak into the eyelid (blepharocele). Magnetic resonance confirmed the result of TC and revealed an area of frontal encephalomalacia. Ibuprofen (800 mg/day) was prescribed, with complete resolution within 20 days. She was evaluated by Neurosurgery with no indication of surgery due to the resolution of the edema and absence of symptoms. Blepharocele is a rare entity that should be considered in the differential diagnosis of unilateral eyelid edema. It can be secondary to an orbital fracture or congenital lesion.